Uji Performa dan Analisis Arsitektur Database MongoDb Standalone, Replikasi, dengan Shard Replika - Kurniasari, Itabella (JATISI, 2025)
Comparation Analysis of MongoDB Standalone, Replica and MongoDB Shard Performance Testing Replication is used to test the response time given by the database. In the Database Management System (DBMS) it can be used to perform basic data management from both local and cloud disks. The main problem that occurs when the data is very large, determining the database architecture is very necessary. Transaction performance per second is an important point when making changes to the database architecture. The method used is waterfall including preparation, analysis and design, implementation, and writing reports. Preparation includes literature studies. Analysis and design to determine the database architecture scheme and select the appropriate tools. Implementation by conducting experiments by installing tools and databases, conducting stress tests with several scenarios that have been created previously. After that, a report is made and conclusions are drawn from the results of the experiment. So that with this test it is expected to be able to provide an overview of the use of database architecture that is in accordance with needs by considering database performance by considering vertical or horizontal scaling. The goal is to suggest options with the best performance, best resources, and minimum costs. This research is important because the research results show that the minimum specifications for a production environment are to use replicas, while the ideal architecture uses MongoDB Sharding with 33.67% on insert and 33.36% on select. This is obtained from considerations of response time, throughput, and database features.